Sinless, Sonless and Seal of Prophets: Muḥammad and Kor 33, 36-40, Revisited - Powers, David Stephan (Arabica, 2020)
In his article, “Between History and Exegesis: the Origins and Transformation of the Story of Muḥammad and Zaynab bt Ǧaḥš,” published in Arabica, 65/1-2 (2018), p. 31-63, Andreas Görke argues that the reference in Kor 33, 37 to Muḥammad’s marriage to the former wife of a man named Zayd “seems to refer to an historical event” and that later exegetical expansions of the episode are based on an “historical kernel.” He adds that these exegetical expansions were modeled on the encounter between David and Bathsheba in II Samuel 11-12 and that the connection between the Islamic and biblical episodes stands at the beginning of the Muslim “preoccupation” with v. 37. Building upon Görke’s scholarship, I show how the early Muslim community created a plausible Sitz im Leben for the episode; establish with greater precision the starting point of the Muslim “preoccupation” with the connection between Muḥammad’s marriage to Zayd’s former wife and David’s marriage to the wife of Uriah the Hittite; and suggest that the qurʾānic treatment of the episode contains a seed of what would become the doctrine of ʿiṣma or the impeccability of prophets. Finally, I propose that the important question for historians is not the event to which the episode purportedly refers but rather the larger geo-political context for the emergence of the qurʾānic proclamation that Muḥammad is ḫātam al-nabiyyīn or the Seal of Prophets. To this end, I seek to shift the scholarly gaze from a domestic crisis in the household of Muḥammad in Medina ca AH 5 to early Christian polemics against Islam and its Prophet and to Byzantine imperial ideology.